To the Problem of Relation of Sociability and Aggression of Personality with Manifestation of Conflict Behavior Styles - D A Tolstova (Peoples' Friendship University of Russia (RUDN University), 2013)
The article considers the results of the study of the relationship of personality traits (for example, sociability and aggression) with the styles of behavior in conflict, carried out in line with the system-functional approach developed by Alexander I. Krupnov. It also analyzes the results of the joint factor analysis of the variables of sociability, aggression and the styles of behavior in conflict in the two groups of respondents: the young people involved and not involved in social Latin dances.